2006
DOI: 10.1074/jbc.m508131200
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the Amino Terminus of the Cystic Fibrosis Transmembrane Conductance Regulator Enhance Endocytosis

Abstract: Efficient endocytosis of the cystic fibrosis transmembrane conductance regulator (CFTR) is mediated by a tyrosine-based internalization signal in the CFTR carboxyl-terminal tail 1424 YDSI 1427 . In the present studies, two naturally occurring cystic fibrosis mutations in the amino terminus of CFTR, R31C, and R31L were examined. To determine the defect that these mutations cause, the Arg-31 mutants were expressed in COS-7 cells and their biogenesis and trafficking to the cell surface tested in metabolic pulse-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 33 publications
0
54
0
Order By: Relevance
“…Previous studies have shown that increasing CFTR internalization or decreasing endocytic recycling do not necessarily affect the metabolic stability of mature CFTR. For example, the R31L or N287Y mutations may introduce a nonnative internalization motif in CFTR and result in increased plasma membrane internalization (8,9). Additionally, the deletion of the C-terminal PDZ binding motif results in decreased apical surface expression, which reflects less efficient recycling and not a change in endocytosis rates (60).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that increasing CFTR internalization or decreasing endocytic recycling do not necessarily affect the metabolic stability of mature CFTR. For example, the R31L or N287Y mutations may introduce a nonnative internalization motif in CFTR and result in increased plasma membrane internalization (8,9). Additionally, the deletion of the C-terminal PDZ binding motif results in decreased apical surface expression, which reflects less efficient recycling and not a change in endocytosis rates (60).…”
Section: Discussionmentioning
confidence: 99%
“…CFTR mutations are functionally categorized by defects in early biosynthesis and folding (class I, II, and V), impaired chloride channel activity (class III and IV), or destabilization of the mature protein (1)(2)(3). The study of CFTR mutations has provided important insights into the regulation of virtually all aspects of CFTR biology including biosynthesis (4,5), gating (6,7), endocytosis (8,9), and degradation (3,10). Current therapeutic strategies are targeting the basic defects associated with mutant CFTR proteins with the goal of correcting these defects in vivo (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Jurkuvenaite et al (42) recently studied R31C and R31L, two CF mutations in the N terminus of CFTR that affect the first AFT (R 29 QR 31 ). Their data demonstrate enhanced internalization from the cell surface, which suggests that some of the reduction in the steady-state levels of band C that we observed with F508del-4RK-CFTR might be explained by enhanced internalization.…”
Section: Rk and G550e Rescue F508del-cftr Channel Gating With Differentmentioning
confidence: 99%
“…The cells were then transferred to a 378C incubator and cultured for 0 to 12 hours in the presence or absence of 10 mM corr-4a in OPTIMEM (Invitrogen) medium supplemented with 2% (vol/vol) FBS. Cell surface glycoproteins were biotinylated as described previously (23). CFTR was immunoprecipitated with a monoclonal antibody to CFTR (24-1) coupled to protein G agarose, run on 8% SDS-PAGE gels, and transferred to polyvinylidene difluoride membranes (Bio-Rad, Hercules, CA).…”
Section: Cftr Cell Surface Half-life Experimentsmentioning
confidence: 99%
“…Immunoprecipitation reactions were performed for 2 hours at 48C. Immunoprecipitated proteins were in vitro phosphorylated and visualized by SDS-PAGE followed by autoradiography and phosphorimaging, or by SDS-PAGE followed by Western blotting (23).…”
Section: Immunoprecipitationmentioning
confidence: 99%